Access policies of electronic resources of selected academic libraries in Metro Manila - Edianon, Neizl S. (School of Library and Information Studies, University of the Philippines Diliman, 2017)
Aiming to provide library users' access to electronic resources for their research needs, this study examined the access policy for electronic resources of selected academic libraries in Metro Manila. The study focused on the member libraries of the Mendiola Consortium and the Aurora Boulevard Consortium. Of the 12 member libraries, only 7 head/chief librarians or library staffs knowledgeable of the member libraries access policy were successfully interviewed. Out of the 7 member libraries, only 5 of them have access policies which were then analyzed and examined.